Application of metaverses and the virtual reality in teaching (2019)
Develop a literature review of the use of metaverses and virtual reality focused on teaching. This article was developed under an exploratory, descriptive methodology; using the following categories: metaverses, virtual reality, and teaching, a search was made in the Science, Scopus and web Science databases, obtaining one hundred reference articles. Education is going through stages of improvement, where the use of new tools helps to promote education. The use of virtual platforms focused on virtual reality, and metaverses are, in essence, the tools for the best-cataloged modern teaching, where this proved to be useful for education.